Spatial distribution of conspecific genotypes within chimeras of the branching coral Stylophora pistillata - Gabriele Guerrini; Dor Shefy; Jacob Douek; Nadav Shashar; Tamar L. Goulet; Baruch Rinkevich (Scientific Reports, 2021)
Abstract Chimerism is a coalescence of conspecific genotypes. Although common in nature, fundamental knowledge, such as the spatial distribution of the genotypes within chimeras, is lacking. Hence, we investigated the spatial distribution of conspecific genotypes within the brooding coral Stylophora pistillata, a common species throughout the Indo-Pacific and Red Sea. From eight gravid colonies, we collected planula larvae that settled in aggregates, forming 2–3 partner chimeras. Coral chimeras grew in situ for up to 25 months. Nine chimeras (8 kin, 1 non-related genotypes) were sectioned into 7–17 fragments (6–26 polyps/fragment), and genotyped using eight microsatellite loci. The discrimination power of each microsatellite-locus was evaluated with 330 ‘artificial chimeras,’ made by mixing DNA from three different S. pistillata genotypes in pairwise combinations. In 68% of ‘artificial chimeras,’ the second genotype was detected if it constituted 5–30% of the chimera. Analyses of S. pistillata chimeras revealed that: (a) chimerism is a long-term state; (b) conspecifics were intermixed (not separate from one another); (c) disproportionate distribution of the conspecifics occurred; (d) cryptic chimerism (chimerism not detected via a given microsatellite) existed, alluding to the underestimation of chimerism in nature. Mixed chimerism may affect ecological/physiological outcomes for a chimera, especially in clonal organisms, and challenges the concept of individuality, affecting our understanding of the unit of selection.